Comparative efficacies of Antimicrobial Catheter Lock Solutions for Fungal Biofilm Eradication in an in vitro model of Catheter-Related Fungemia. (4th October 2017) - Rosenblatt, Joel; Reitzel, Ruth; Vargas-Cruz, Nylev; Chaftari, Anne-Marie; Hachem, Ray Y; Raad, Issam
Abstract: Background: Fungal catheter-related bloodstream infections (CRBSIs), primarily due to Candida species, account for over 12% of all CRBSIs and have been progressively increasing in prevalence. They present significant health and economic burdens and high rates of mortality. Antimicrobial catheter lock solutions are an important prophylactic option for preventing fungal CRBSIs. In this study we compared the effectiveness of two FDA-approved catheter lock solutions (heparin and saline) and three experimental antimicrobial catheter lock solutions, 30% Citrate, Taurolidine-Citrate-Heparin (TCH), and Nitroglycerin-Citrate-Ethanol (NiCE). Methods: All solutions were tested in an in vitro model of yeast biofilm eradication. The yeast tested were five different strains of Candida clinical isolates from cancer patients who contracted CRBSIs. Time-to-biofilm-eradication was assessed in the model with 15, 30 and 60 minute exposures to the lock solutions. Results: Only the NiCE lock solution was able to fully eradicate all fungal biofilms within 60 minutes. Neither 30% citrate nor TCH was able to fully eradicate any of the Candida biofilms in this time frame. The NiCE lock solution was significantly superior to TCH in eradicating biofilms of five different Candida species ( P = 0.002 for all). Conclusion: NiCE lock showed significant efficacy compared with all solutions tested indicating NiCE has the potential to be used as an antifungal lock solution in high-risk settings where CRBSI caused by Candida is predominant. Disclosures: J. Rosenblatt, Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a and Shareholder, Licensing agreement or royalty; UT MD Anderson Cancer Center: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a s and Scientific Advisor, Licensing agreement or royalty; I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty